Case Study: HLA incompatible platelet infusion to allow emergency salvage HCT in a patient with primary graft failure due to donor specific HLA antibody - Goddard, Louise; Moses, Jonathan; Chu, Gerard Joseph; Carroll, Robert P. (Frontiers in Immunology, 2026)
A patient with myelodysplasia received a haploidentical hematopoietic stem cell transplant (HCT). Pre-transplant HLA antibody screening showed no detectable donor-specific antibodies (DSAs). Post-transplant, the patient developed an anti-HLA-A2 antibody, likely due to a memory B-cell response. This immune response led to platelet transfusion refractoriness and graft failure. The patient engrafted following a second stem cell infusion from the same haploidentical donor, using both HLA compatible platelets, to support initial platelet transfusion refractoriness (PTR) following primary stem cell infusion, and HLA-A*02 expressing platelets, to adsorb the circulating anti-A2 prior to the re-infusion.